Experimental deep tissue pain in wrist extensors--a model of lateral epicondylalgia - Slater, Helen; Arendt-Nielsen, Lars; Wright, Tony (Elsevier, 2003)
The aim of this experimental study was to develop an in vivo model demonstrating sensory and motor interactions comparable to those seen in patients presenting with lateral epicondylalgia (i.e., deep tissue pain and hyperalgesia localised to specific sites in the wrist extensors, attenuation of wrist extension force). The effect of saline-induced deep pain combined with delayed onset muscle soreness (DOMS) on deep tissue sensitivity and motor function in wrist extensors was examined. Muscle pain intensity (visual analogue scale: VAS), distribution, and quality were assessed in 12 subjects. Pressure pain thresholds (PPTs) were recorded at five different sites around the elbow. Maximal wrist extension force was recorded. In the absence of DOMS, hypertonic saline administrated into different parts of the wrist extensors (extensor carpi radialis brevis, supinator, common extensor origin) induced significantly (P < 0:05) higher VAS scores and larger pain areas compared with a control injection of isotonic saline. The typical quality of saline-induced pain was described as ''drilling'', ''taut'', ''nagging'' and ''intense''. In non-exercised wrist extensors, hyperalgesia to pressure was not detected during saline-induced pain but maximal wrist extensor force decreased significantly (P < 0:05) compared with pre-pain recordings and recordings post isotonic saline. DOMS induced by eccentric wrist extension contractions generated moderate levels of soreness but no resting pain up to 24 h post exercise. PPTs and maximal wrist extension force were significantly decreased (P < 0:05) during DOMS compared with baseline and 7 days post exercise (P < 0:05). VAS scores to injection of hypertonic saline into the DOMS arm were significantly increased (P < 0:05) compared with injections into the unexercised arm. This is another manifestation of muscle hyperalgesia. Saline-induced pain combined with DOMS further decreased maximal wrist extension force (P < 0:05). The simultaneous deep tissue pain and hyperalgesia linked with force attenuation support the use of the saline-induced deep tissue pain combined with DOMS as an experimental model simulating the clinical sensorimotor correlates of lateral epicondylalgia.